2020
DOI: 10.1200/jco.20.00203
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan, Temozolomide, and Dinutuximab With GM-CSF in Children With Refractory or Relapsed Neuroblastoma: A Report From the Children’s Oncology Group

Abstract: PURPOSE The combination of irinotecan, temozolomide, dintuximab, and granulocyte-macrophage colony-stimulating factor (I/T/DIN/GM-CSF) demonstrated activity in patients with relapsed/refractory neuroblastoma in the randomized Children’s Oncology Group ANBL1221 trial. To more accurately assess response rate and toxicity, an expanded cohort was nonrandomly assigned to I/T/DIN/GM-CSF. PATIENTS AND METHODS Patients were eligible at first relapse or first designation of refractory disease. Oral T and intravenous (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
112
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 39 publications
0
112
0
5
Order By: Relevance
“…Finally, anti-GD2 is increasingly used for immunotherapy in high-risk NB 36 . Currently, after surgery, but ongoing trials will assess the advantage of neoadjuvant treatment 37 , 38 . Therefore, we also confirmed that anti-GD2-IRDye800CW can still detect NB tissue after upfront anti-GD2 treatment, further validating the wide range of patients that could potentially benefit from anti-GD2-IRDye800CW guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, anti-GD2 is increasingly used for immunotherapy in high-risk NB 36 . Currently, after surgery, but ongoing trials will assess the advantage of neoadjuvant treatment 37 , 38 . Therefore, we also confirmed that anti-GD2-IRDye800CW can still detect NB tissue after upfront anti-GD2 treatment, further validating the wide range of patients that could potentially benefit from anti-GD2-IRDye800CW guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Even more importantly, improvement in OS also reflects a novel paradigm in the anti-GD2 immunotherapy era: relapse is no longer an invariably lethal event. In the current era of anti-GD2 immunotherapy relapses occur more limited, isolated, less aggressive, and more amenable to control ( Kushner et al, 2015 ; Mody et al, 2017 ; Mody, 2020 ). Further evidence of the overall survival benefit resulting from anti-GD2 immunotherapy is the outcome of the refractory cohort in this study and others ( Kushner et al, 2015 ; Mody et al, 2017 ; Mody, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, there is a relatively poor response when used alone in the setting of bulk tumor 66 , which is likely to contain a significant portion of immunologically quiescent adrenergic cells. However, responses are much better when anti-GD2 therapy is combined with chemotherapy31,32 , which may allow for targeting of both states simultaneously.Immunocompetent animal models will be needed to understand the impact of the differences in inflammatory sensing between MES and ADRN states in vivo and a lack of such experiments is a limitation of the current study. This provides a challenge, however.…”
mentioning
confidence: 99%